The rising sea [compact disc, unabridged] : a novel from the NUMA files - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. NUMA files., 2018)
An alarming rise in the world's sea levels--much larger than could be accounted for by glacier melt--sends Kurt Austin, Joe Zavala, and the rest of the NUMA scientific team rocketing around the globe in search of answers.